2023
DOI: 10.3390/cells12071005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Demethylation of the TGFβ1 mRNA Promotes Myoblast Proliferation via Activating the SMAD2 Signaling Pathway

Abstract: Recent evidence suggested that N6-methyladenosine (m6A) methylation can determine m6A-modified mRNA fate and play an important role in skeletal muscle development. It was well known that transforming growth factor beta 1 (TGFβ1) is involved in a variety of cellular processes, such as proliferation, differentiation, and apoptosis. However, little is known about the m6A-mediated TGFβ1 regulation in myogenesis. Here, we observed an increase in endogenous TGFβ1 expression and activity during myotube differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…It was observed that silencing FTO impaired mitochondrial biogenesis and energy production, attributable to the downregulation of the mTOR and PGC-1α [ 159 ]. Further investigation revealed that m6A modification of the 5′UTR of TGFβ1 mRNA facilitates its degradation, with FTO influencing these modifications to hinder myoblast differentiation [ 160 ]. Experiments in genetically engineered mice demonstrated that FTO overexpression did not alter skeletal muscle mass [ 220 ], whereas FTO deficiency compromised skeletal muscle development [ 159 ].…”
Section: The Role Of Epigenetic In Skeletal Muscle Atrophymentioning
confidence: 99%
“…It was observed that silencing FTO impaired mitochondrial biogenesis and energy production, attributable to the downregulation of the mTOR and PGC-1α [ 159 ]. Further investigation revealed that m6A modification of the 5′UTR of TGFβ1 mRNA facilitates its degradation, with FTO influencing these modifications to hinder myoblast differentiation [ 160 ]. Experiments in genetically engineered mice demonstrated that FTO overexpression did not alter skeletal muscle mass [ 220 ], whereas FTO deficiency compromised skeletal muscle development [ 159 ].…”
Section: The Role Of Epigenetic In Skeletal Muscle Atrophymentioning
confidence: 99%